Re-emergence of methicillin susceptibility in a resistant lineage of Staphylococcus aureus. (20th January 2017) - Ledda, Alice; Price, James R.; Cole, Kevin; Llewelyn, Martin J.; Kearns, Angela M.; Crook, Derrick W.; Paul, John; Didelot, Xavier
Abstract : Objectives: MRSA is a leading cause of hospital-associated infection. Acquired resistance is encoded by the mecA gene or its homologue mecC, but little is known about the evolutionary dynamics involved in gain and loss of resistance. The objective of this study was to obtain an expanded understanding of Staphylococcus aureus methicillin resistance microevolution in vivo, by focusing on a single lineage. Methods: We compared the whole-genome sequences of 231 isolates from a single epidemic lineage [clonal complex 30 (CC30) and spa -type t018] of S. aureus that caused an epidemic in the UK. Results: We show that resistance to methicillin in this single lineage was gained on at least two separate occasions, one of which led to a clonal expansion around 1995 presumably caused by a selective advantage. Resistance was, however, subsequently lost in vivo by nine strains isolated between 2008 and 2012. We describe the genetic mechanisms involved in this loss of resistance and the imperfect relationship between genotypic and phenotypic resistance. Conclusions: The recent re-emergence of methicillin susceptibility in this epidemic lineage suggests a significant fitness cost of resistance and reduced selective advantage following the introduction in the mid-2000s of MRSA hospital control measures throughout the UK.